2019
DOI: 10.3390/ma12101628
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Low Methoxyl Pectin/Gelatin/Carboxymethyl Cellulose Absorbent Hydrogel Film for Wound Dressing Applications

Abstract: In this study, hydrogel films composed of low methoxyl pectin (LMP), gelatin, and carboxymethyl cellulose (CMC) were fabricated. Glycerin was used as a plasticizer while glutaraldehyde (Glu) and calcium chloride (CaCl2) were used as crosslinking agents in film preparation. Hydrogel films were morphologically characterized and evaluated for mechanical properties. In addition, the investigations for fluid uptake ability, water retention capacity, water vapor transmission rate, and integrity value of the invented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…CMC is widely used to improve the characteristics and effectiveness of various wound dressing and wound healing materials in various clinical applications due to their excellent binding capacity to the internal body cells, biocompatibility (i.e., with skin, bone, and mucous membranes), and strong hydrophilic property (due to the presence of anionic carboxylic and hydroxyl groups in internal network structure and surface as well) [ 246 , 247 ]. Furthermore, blending capability with various water-soluble organic polymers such as poly-(vinyl alcohol) (PVA), poly-(ethylene glycol), etc., have widened the application field of CMC-based biomaterials in wound dressing purposes [ 248 , 249 ]. In this regard, numerous structures of such materials have been used.…”
Section: Application Of Cmcmentioning
confidence: 99%
See 1 more Smart Citation
“…CMC is widely used to improve the characteristics and effectiveness of various wound dressing and wound healing materials in various clinical applications due to their excellent binding capacity to the internal body cells, biocompatibility (i.e., with skin, bone, and mucous membranes), and strong hydrophilic property (due to the presence of anionic carboxylic and hydroxyl groups in internal network structure and surface as well) [ 246 , 247 ]. Furthermore, blending capability with various water-soluble organic polymers such as poly-(vinyl alcohol) (PVA), poly-(ethylene glycol), etc., have widened the application field of CMC-based biomaterials in wound dressing purposes [ 248 , 249 ]. In this regard, numerous structures of such materials have been used.…”
Section: Application Of Cmcmentioning
confidence: 99%
“…Furthermore, pore-sizes of the hydrogels were proven to be flexible and could be tailored by varying the aspect ratio and concentration of the PVA in the hydrogel. In the same year, another research group of Jantrawut et al (2019) [ 248 ] developed a low methoxyl pectin/gelatin/CMC-based bi-layered hydrogel film that also exhibited a high fluid uptake capability and water retention capacity with a high integrity value. Additionally, well-controlled drug release of the hydrogel films loaded with povidone-iodine demonstrated its potentialities to be used as an alternative vehicle for the delivery of aseptic and/or antibiotics to the moist wound sites to accelerate wound healing without any kinds of posterior bacterial infections.…”
Section: Application Of Cmcmentioning
confidence: 99%
“…There is a vast number of materials available for wound dressing, currently under investigation for different types of wounds and different treatment approaches [1][2][3][4]. The type, depth, and location of a wound, in addition to the extent of damage, the amount of wound exudates and the presence of an infection in the wound site, are key factors in the selection of dressing type.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium swelling ratio of the composite films depended on the kinds of anionic polysaccharides involved. It is known that HYA and CMC have excellent water-holding abilities [34,35]. The results that films containing them also showed high equilibrium swelling ratio (Table 3) indicated that anionic polysaccharide properties were maintained in the composite films.…”
mentioning
confidence: 91%